A Wolbachia wMel transinfection in Aedes albopictus is not detrimental to host fitness and inhibits Chikungunya virus - Blagrove, MS; Arias-Goeta, C; Di Genua, C; Failloux, AB; Sinkins, S (Public Library of Science, 2013)
BACKGROUND: Wolbachia inherited intracellular bacteria can manipulate the reproduction of their insect hosts through cytoplasmic incompatibility (CI), and certain strains have also been shown to inhibit the replication or dissemination of viruses. Wolbachia strains also vary in their relative fitness effects on their hosts and this is a particularly important consideration with respect to the potential of newly created transinfections for use in disease control. METHODOLOGY/PRINCIPAL FINDINGS: In Aedes albopictus mosquitoes transinfected with the wMel strain from Drosophila melanogaster, which we previously reported to be unable to transmit dengue in lab challenges, no significant detrimental effects were observed on egg hatch rate, fecundity, adult longevity or male mating competitiveness. All these parameters influence the population dynamics of Wolbachia, and the data presented are favourable with respect to the aim of taking wMel to high population frequency. Challenge with the chikungunya (CHIKV) virus, for which Ae. albopictus is an important vector, was conducted and the presence of wMel abolished CHIKV dissemination to the saliva. CONCLUSIONS/SIGNIFICANCE: Taken together, these data suggest that introducing wMel into natural Ae. albopictus populations using bidirectional CI could be an efficient strategy for preventing or reducing the transmission of arboviruses by this species.